Dualism of Sanctions in Unlawful Acts: Between Civil Damages and Criminal Punishment - Yuliana, Tora; Marzuki, Agus; Malagano, Tahura; Susanti, Ino; Nurahman, Dwi; Sukardi, Dina Haryati; Muhadi (LifeSciFi, 2025)
Sanction dualism often arises in offenses such as fraud, embezzlement, or persecution, where a single act violates public legal norms and simultaneously causes personal harm to individuals. This study explores the concept of sanction dualism the simultaneous imposition or potential overlap of criminal and civil sanctions in cases of unlawful acts within the Indonesian legal system. Using a normative juridical method, the study relies on legislative and conceptual approaches grounded in the theory of legal integration, which supports a cross-branch legal framework. The research identifies two key issues: how the legal system conceptualizes sanction dualism and how it manages the harmonization between criminal and civil law. The findings highlight that although Indonesia permits the application of dual sanctions, there are significant procedural and institutional challenges. These include limited integration of civil claims within criminal proceedings, a lack of clear technical guidelines, and inadequate protection of victims’ rights. Consequently, legal processes often become fragmented and fail to deliver substantive justice. The study recommends regulatory reform, improved coordination among legal institutions, and stronger adoption of integrative legal approaches. These efforts are crucial for achieving a legal process that is fair, efficient, and capable of restoring both legal certainty for perpetrators and justice for victims. Metode yang digunakan dalam penelitian ini adalah metode yuridis normatif dengan pendekatan peraturan perundang-undangan, pendekatan konseptual, serta studi kasus yang relevan. Teori yang menjadi dasar analisis adalah teori integrasi hukum yang menjelaskan perlunya pendekatan lintas-cabang hukum dalam menangani satu perbuatan melawan hukum. Hasil penelitian menunjukkan bahwa sistem hukum Indonesia secara normatif memungkinkan pemberlakuan dualisme sanksi, namun pelaksanaannya masih menghadapi tantangan dalam hal prosedur, kelembagaan, dan perlindungan hak-hak korban. Meskipun KUHAP mengatur kemungkinan penggabungan gugatan perdata dalam proses pidana, penerapannya masih terbatas dan jarang digunakan. Selain itu, belum adanya pedoman teknis yang jelas menyebabkan proses hukum sering berjalan secara terpisah dan tidak sinkron, sehingga berisiko mengabaikan keadilan substantif. Penelitian ini merekomendasikan perlunya harmonisasi yang lebih sistematis antara hukum pidana dan perdata, baik melalui pembaruan regulasi, peningkatan koordinasi antarlembaga penegak hukum, maupun penguatan pemahaman aparat terhadap pendekatan integratif. Tujuannya adalah agar proses hukum dapat berjalan secara efisien, adil, dan komprehensif, sekaligus menjamin pemulihan hak korban dan kepastian hukum bagi pelaku.